Tipe Kepribadian Sanguinis Tokoh Magi Diela dalam Novel Perempuan yang Menangis kepada Bulan Hitam Karya Dian Purnomo - Erlina Zahar; Ardinah Ardinah (Universitas Batanghari Jambi, 2022)
This study aims to describe the sanguine personality type of Magi Diela in Dian Purnomo's novel Perempuan Yang Crying to Bulan Hitam. In carrying out this research, the researcher used a qualitative descriptive research type. The data from this study were taken from quotations related to the sanguine personality type of the character Magi Diela in Dian Purnomo's novel Perempuan Yang Crying to Bulan Hitam. The source of the data for this research comes from the novel Women Who Cry to the Black Moon by Dian Purnomo which was published by Gramedia Pustaka Utama in 2020. The data collection technique in this study was to use documentation techniques which were used as data to be analyzed with a structural approach. This technique is used by the researchers to describe the sanguine personality type of Magi Diela in the novel Perempuan Yang Crying to Bulan Hitam by Dian Purnomo. As for the number of quotes related to the sanguine personality type of Magi Diela's character in Dian Purnomo's novel Perempuan Yang Crying to Bulan Hitam, there were 61 findings. The sanguine personality type of Magi Diela in the novel Perempuan Yang Crying to the Black Moon by Dian Purnomo is an individual who has an open and sociable nature. So like new experiences and will be excited in facing life's challenges.